A Computer Simulation Model For Surface Mine Reclamation Planning - Volume IV: User's Manual For OPMHS/2 - R. V. Ramani (The National Institute for Occupational Safety and Health (NIOSH), 1985)
This volume is the fourth of a four-volume final report on research carried out under a contract from the U.S. Bureau of Mines on the development of a computer simulation model for surface mine reclamation planning. The other volumes are titled as follows: Volume I: Ore Reserve Estimation, Volume II: Dragline Model, and Volume III: Mine Coordinate Generator System. The Open Pit Materials Handling Simulator (OPMHS) was first developed" in 1971 and modified and updated in 1975. The present work is an update of the 1975 version and provides a direct link between the geology and reserves system and the various activities of the mining equipment in a mining system. Also, the modeling techniques in OPMHS/2 have incorporated a flexible method for describing various equipment (shovels, trucks, belts, trains, etc.), locations, their sequence of operations, place changes, and their interactions. These features allow for studying mining equipment selection, mining method analysis and reclamation planning. This report describes the Open Pit Materials Handling Simulator Version 2 (OPMHS/2). The report details the program features, operation, and application. Through an extensive set of appendices, the data input sequence, input variable definitions, sample data listing and program output are presented in detail.